Improvement in adenoma detection using a novel artificial intelligence-aided polyp detection device - Shaukat, Aasma; Colucci, Daniel; Erisson, Lavi; Phillips, Sloane; Ng, Jonathan; Iglesias, Juan Eugenio; Saltzman, John R.; Somers, Samuel; Brugge, William (Endoscopy International Open, 2021)
Background and study aims Detecting colorectal neoplasia is the goal of high-quality screening and surveillance colonoscopy, as reflected by high adenoma detection rate (ADR) and adenomas per colonoscopy (APC). The aim of our study was to evaluate the performance of a novel artificial intelligence (AI)-aided polyp detection device, Skout, with the primary endpoints of ADR and APC in routine colonoscopy.Patients and methods We compared ADR and APC in a cohort of outpatients undergoing routine high-resolution colonoscopy with and without the use of a real-time, AI-aided polyp detection device. Patients undergoing colonoscopy with Skout were enrolled in a single-arm, unblinded, prospective trial and the results were compared with a historical cohort. All resected polyps were examined histologically.Results Eighty-three patients undergoing screening and surveillance colonoscopy at an outpatient endoscopy center were enrolled and outcomes compared with 283 historical control patients. Overall, ADR with and without Skout was 54.2 % and 40.6 % respectively (P = 0.028) and 53.6 % and 30.8 %, respectively, in screening exams (P = 0.024). Overall, APC rate with and without Skout was 1.46 and 1.01, respectively, (P = 0.104) and 1.18 and 0.50, respectively, in screening exams (P = 0.002). Overall, true histology rate (THR) with and without Skout was 73.8 % and 78.4 %, respectively, (P = 0.463) and 75.0 % and 71.0 %, respectively, in screening exams (P = 0.731).Conclusion We have demonstrated that our novel AI-aided polyp detection device increased the ADR in a cohort of patients undergoing screening and surveillance colonoscopy without a significant concomitant increase in hyperplastic polyp resection. AI-aided colonoscopy has the potential for improving the outcomes of patients undergoing colonoscopy.